2017
DOI: 10.1016/j.bbabio.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Photosystem II-cyclic electron flow powers exceptional photoprotection and record growth in the microalga Chlorella ohadii

Abstract: The desert microalga Chlorella ohadii was reported to grow at extreme light intensities with minimal photoinhibition, tolerate frequent de/re-hydrations, yet minimally employs antenna-based non-photochemical quenching for photoprotection. Here we investigate the molecular mechanisms by measuring Photosystem II charge separation yield (chlorophyll variable fluorescence, Fv/Fm) and flash-induced O yield to measure the contributions from both linear (PSII-LEF) and cyclic (PSII-CEF) electron flow within PSII. Cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 73 publications
1
49
0
1
Order By: Relevance
“…An interesting case of almost total uncoupling of fluorescence‐based estimates of PSII activity and oxygen evolution in microalgae is Chlorella ohadii , a green alga isolated from desert crust of Israel (Treves et al ). The uncoupling of the two parameters in C. ohadii was assigned to the proposed cyclic electron flow pathway within PSII (Treves et al , Ananyev et al ), a pathway suggested to participate in photoprotection in excess light also in the diatom P. tricornutum (Feikema et al ).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting case of almost total uncoupling of fluorescence‐based estimates of PSII activity and oxygen evolution in microalgae is Chlorella ohadii , a green alga isolated from desert crust of Israel (Treves et al ). The uncoupling of the two parameters in C. ohadii was assigned to the proposed cyclic electron flow pathway within PSII (Treves et al , Ananyev et al ), a pathway suggested to participate in photoprotection in excess light also in the diatom P. tricornutum (Feikema et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Polarographic measurements of flash‐induced O 2 evolution patterns (FIOPs) in plastids were performed in the presence of DMBQ as an electron acceptor using in‐house Clark‐type Pt/Ir electrode with a thin‐layer microchamber configuration described recently (Ananyev et al , Ananyev et al ). The electrode was equipped with a thin (∼0.5 μm) polyethylene membrane which prevented the interference of DMBQ with a current of the cathode–anode system.…”
Section: Methodsmentioning
confidence: 99%
“…With exception of a few known unique photoinhibition-tolerant species (Fukuda et al 2008, Ananyev et al 2017, all photosynthetic organisms, under environmental stress and excessive light energy, are prone to photoinhibition, which strongly affects their photosynthetic activity, growth and productivity. To cope with photodamage, mature plants have developed diverse photoprotection mechanisms and are capable of reassembly and replacement of the damaged PSII centers via a PSII repair cycle (Nixon et al 2010, Takahashi and Badger 2011, Järvi et al 2015, Pinnola and Bassi 2018.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Turpin and Bruce [40] discovered that ammonia assimilation could induce state transitions of photosynthesis, and nonphotochemical quenching of PSII was associated with uorescence yield of PSI increase during ammonia assimilation due to high energy requirement. PSII is surrounded by cyclic electron ow which can also generate ATP for potential nutrient assimilation [43]. 2) The high expression of PSII under nutrient stress is due to its self-repairment and re-assembly to guarantee its function [44,45].…”
Section: Photosynthetic Adaptation Of Symbiodiniaceae To Nutrient Enrmentioning
confidence: 99%